Perencanaan Strategis PT. Indofarma Global Medika - Amrius; Derriawan; Zulkifli (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
Every company in its activities need to build or create a plan in order to reach its goal (if you fail to plan, you plan to fail) that's the reason build a good strategic plan and be implemented properly is a must for companies. In order to create a good formulation strategic, needed analysis and a correct strategic tools, Three steps Strategic Framework's used in this theses namely Input Stage, Matching Stage and Decision Stage. The result in matching stage analysis, indicates lndofarma Global Medika's position in defensive quadrant with turnaround as an main strategic ,and retrenchment, divestiture, and liquidation another alternative strategic. Implementation of this alternative strategic will implicate to revision of some policy, retrench of business unit/branches, changing policy, changing, adding product portofolio, reduce of human resource, customer, networking coverage, capital (capex), and liquiditation of the company. This will cause value added of IGM.